2019
DOI: 10.1109/access.2019.2952381
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Accuracies of Age Estimation With Heterogeneous Databases Using Modified CycleGAN

Abstract: Age estimation using face images has been widely employed across various fields. Because the characteristics of face images usually vary greatly depending on race, camera type, lighting, and other environmental factors, the recognition ability of untrained heterogeneous face image databases is not accurate by previous methods. Therefore, various attempts have been made where different heterogeneous databases were combined to enable training; however, the training time is extended and diverse environmental vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 42 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…Both the MegaAge Asian [16] and Asian face age dataset (AFAD) [11] include only the Asian face images. In previous research [10], they confirmed that the age estimation accuracies with Morph database were higher than those with AFAD, and the age estimation accuracies with Morph database were also reported to be higher than those with MegaAge Asian in [20]. From these results, we can estimate that the more distinctive changes including facial shape and texture occur in Caucasian race than those in Asian according to face aging, which causes the age estimation to be easier with the face images of Caucasian compared to those of Asian.…”
Section: B Facial Image Generation By the Enhanced Cycle Generative mentioning
confidence: 52%
See 4 more Smart Citations
“…Both the MegaAge Asian [16] and Asian face age dataset (AFAD) [11] include only the Asian face images. In previous research [10], they confirmed that the age estimation accuracies with Morph database were higher than those with AFAD, and the age estimation accuracies with Morph database were also reported to be higher than those with MegaAge Asian in [20]. From these results, we can estimate that the more distinctive changes including facial shape and texture occur in Caucasian race than those in Asian according to face aging, which causes the age estimation to be easier with the face images of Caucasian compared to those of Asian.…”
Section: B Facial Image Generation By the Enhanced Cycle Generative mentioning
confidence: 52%
“…A modified CycleGAN-based age estimation method based on race transformations of facial images has been proposed [20]. This study used a generator similar to the conventional CycleGAN [37].…”
Section: B Using Heterogeneous Databases For Training and Testing 1)mentioning
confidence: 99%
See 3 more Smart Citations